The Influence of Workload on Work–Life Balance among Employees in the Mining Sector - Nilam Puspitasari; Nurina Aprilya; Muhammad Abdul Rauf; Muhammad Ihsan Alfarizi (Journal of Language and Health, 2025)
Work–life balance (WLB) has become a strategic concern in high-demand industries such as mining, where extended shifts, heavy workloads, and family demands can undermine employee well-being and organisational sustainability. Although workload is recognised as a key antecedent of WLB, empirical evidence from Indonesia’s mining sector remains limited. This study aimed to examine the influence of workload on WLB among employees of PT Bumi Suksesindo, a copper and gold mining company in Banyuwangi, Indonesia. An analytic observational study with a cross-sectional design was conducted among 100 randomly selected employees. Workload was measured using items adapted from the NASA Task Load Index (NASA-TLX), while WLB was assessed with the Work–Life Balance Scale. Both instruments were tested for validity and reliability before data collection, yielding acceptable content validity and high internal consistency (Cronbach’s alpha = 0.87 for NASA-TLX and 0.84 for WLB Scale). Data were analysed using Pearson correlation, independent t-tests, and multivariate regression with demographic factors as controls. Employees reported moderate to high workload levels (M = 62.3, SD = 11.4) and relatively low WLB (M = 58.7, SD = 10.2). A significant negative correlation was observed between workload and WLB (r = –0.46, p < 0.001). Regression analysis confirmed workload as the strongest predictor of WLB (β = –0.42, p < 0.001), even after adjusting for demographics. Marital status also emerged as significant (β = –0.19, p = 0.032), with married employees reporting lower balance. Other demographic variables showed no meaningful effects. Workload is a critical determinant of WLB in the mining sector, with marital obligations further compounding its effects. The findings support the Job Demands–Resources model, highlighting the need for workload management strategies, flexible scheduling, and supportive policies to safeguard employee well-being and sustain organisational performance.